Nature-Inspired Chiral Structures: Fabrication Methods and Multifaceted Applications - Kim, Da Seul; Kim, Myounggun; Seo, Soonmin; Kim, Ju Hyung (Biomimetics, 2023)
Diverse chiral structures observed in nature find applications across various domains, including engineering, chemistry, and medicine. Particularly notable is the optical activity inherent in chiral structures, which has emerged prominently in the field of optics. This phenomenon has led to a wide range of applications, encompassing optical components, catalysts, sensors, and therapeutic interventions. This review summarizes the imitations and applications of naturally occurring chiral structures. Methods for replicating chiral architectures found in nature have evolved with specific research goals. This review primarily focuses on a top-down approach and provides a summary of recent research advancements. In the latter part of this review, we will engage in discussions regarding the diverse array of applications resulting from imitating chiral structures, from the optical activity in photonic crystals to applications spanning light-emitting devices. Furthermore, we will delve into the applications of biorecognition and therapeutic methodologies, comprehensively examining and deliberating upon the multifaceted utility of chiral structures.
Keywords: chirality; circular polarization; enantiomers; mirror images